New b-value parameter for quantitatively monitoring the structural health of carbon fiber-reinforced composites. (15th February 2022) - Jung, Doyun; Yu, Woong-Ryeol; Ahn, Hyunchul; Na, Wonjin
Highlights: An optimized b -value for the fiber-reinforced composite material is proposed. I b -value is modified using the AE parameters at the crack origin location. The original I b -value increases as the propagation distance increases. A new parameter (C b -value) is maintained independently of propagation distance. Abstract: Carbon fiber-reinforced composites have excellent mechanical properties but are vulnerable to the accumulation of small cracks. This study used acoustic emission (AE) signals to monitor and quantify composite damage. We subjected carbon fiber/epoxy specimens to cyclic loading (10 cycles/step, up to 700 MPa of tensile stress). We obtained AE signals over a wide frequency range that can be used to monitor failure modes. The conventional I b -value decreased with increasing damage and shifted upward as the propagation distance increased. We introduced a new parameter, the composite b -value (C b -value), to analyze AE amplitude distribution at the crack origin. It was demonstrated that the C b -value is independent of sensor location, thus providing accurate information on the overall damage. Finally, a standard value based on the C b –value was suggested as an index of the damage level in composite materials; this is a useful indicator of structural health.